Catalyzing marketing innovation and competitive advantage in the healthcare industry: the value of thinking like an outsider - James K. Elrod; John L. Fortenberry (BMC, 2018)
Abstract Background Marketing arguably is the most critical administrative responsibility associated with the pursuit and realization of growth and prosperity, making prowess in the discipline essential for any healthcare institution, especially given the competitive intensity that characterizes the industry. But in order to truly gain an advantage, healthcare establishments must tap into innovative pathways that their competitors have yet to discover. Here, thinking like an outsider can pay tremendous dividends, as health and medical organizations tend to focus inwardly, limiting their exposure to externally-derived innovations and advancements which often can supply differentiation opportunities. Discussion Some years ago, during a formative period in preparation for expanding its footprint, Willis-Knighton Health System opted to think like an outsider, peering beyond the walls of healthcare institutions in search of tools and techniques that would allow its growth ambitions to be realized. Associated pursuits and subsequent successes created a culture of challenging status quo perspectives, affording innovations and resulting competitive advantages. Marketing advancements, in particular, have been fueled by this outsider mentality, benefiting the institution and its patient populations. This article profiles several of these advancements, discusses the dangers of insular mindsets, and suggests avenues for encouraging broad perspectives. Conclusions Due to extreme competitive intensity and ever-increasing patient needs, health and medical establishments must perform at optimal levels, with marketing efforts playing a critical role in the achievement of such. By shedding status quo perspectives and peering beyond the walls of healthcare institutions, health and medical providers have opportunities to discover new and different marketing approaches for potential use in their own organizations, affording mutual benefits, including all-important competitive advantages.